2022
DOI: 10.1155/2022/5398085
|View full text |Cite|
|
Sign up to set email alerts
|

English Teaching Quality Evaluation Based on Analytic Hierarchy Process and Fuzzy Decision Tree Algorithm

Abstract: China’s economy has become more globalized in the twenty-first century. English has become the primary means of communication and trade between people and other countries as the economy has rapidly developed. As a result, colleges and universities have increased the English proficiency and teaching quality criteria for college students. The success of college instructors’ English instruction is judged using teaching quality as a primary metric. The procedure of assessing the quality of English instruction is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…The quality assurance system of higher education places great importance on the teaching quality of college professors, which serves as a crucial aspect indicating their teaching proficiency [1][2][3] . Evaluating the teaching quality of professors enables the educational management department to gain a systematic, comprehensive, and accurate understanding of the teaching standards and quality across various courses.…”
Section: Introductionmentioning
confidence: 99%
“…The quality assurance system of higher education places great importance on the teaching quality of college professors, which serves as a crucial aspect indicating their teaching proficiency [1][2][3] . Evaluating the teaching quality of professors enables the educational management department to gain a systematic, comprehensive, and accurate understanding of the teaching standards and quality across various courses.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%